Saluran Dan Efesiensi Pemasaran Selada Hidroponik Skala Rumahan Dalam Upaya Peningkatan Perekonomian Keluarga Desa Loru - Sholeh Puja Ramadan; Betty Betty; Adfiyani Fadjar (Journal of Management and Social Sciences, 2023)
The efforts of the Loru village government in order to improve food security and support the improvement of the family economy are by facilitating training for farmers. Loru village collaborated with PT. Nina Agro Jaya conducts Hydroponic Farming training for lettuce plants. The result of this training farmers will be faced with the marketing process. With all kinds of problems that will be faced in the marketing process. Another form of this activity is to describe the hydroponic lettuce marketing channel and to analyze the size of the margin and the efficiency level of hydroponic lettuce marketing. So that later lettuce farmers will have a better understanding of market conditions and be able to independently take certain actions in the marketing process. This activity was carried out in Loru Village, Sigi Biromaru District, Sigi Regency.